Protection of chickens against A/H5N1 virus by plant-based haemagglutinin fused IGMFC - Van, Pham Thi; Huong, Ho Thi; Thu Giang, Nguyen; Ngoc, Pham Bich; Trang, Vu Huyen; Hoang, Phan Trong; Hanh, Tran Xuan; Conrad, Udo; Ha, Chu Hoang (Vietnam Journal of Biotechnology, 2020)
Vaccination is one of the most effective and cost-beneficial interventions for protection of animals against the highly pathogenic A/H5N1 avian influenza virus. Haemagglutinin (HA) is a transmembrane glycoprotein of A/H5N1 virus and is a critical antigen for development of the influenza vaccine. The haemagglutinin-based vaccine produced in plants was demonstrated as a candidate vaccine since it elicited neutralizing antibodies against A/H5N1 virus. In this study, immunogenicity and protective ability of a plant-based recombinant HA antigen which was fused to IgMFc to form oligomerized HA antigen (H5TG oligomer) had been evaluated by vaccination in chickens. Chicken sera after each vaccination were collected for Western blot, ELISA and HI assays. Ten days after the second vaccination, the chickens have been challenged with A/duck/TG/NAVET(3)/2013 virus, clade 1.1. The analysis results showed that the oligomeric recombinant H5TG antigen elicited stronger H5TG-specific IgY antibodies and A/H5N1 clade 1.1 virus-neutralizing antibodies than the H5TGpII trimeric recombinant antigen without fusing IgMFc in vaccinated chickens. Notably, the chicken protection rate against A/H5N1 clade 1.1 virus of the H5TG oligomer antigen was 80% that is not significantly lower than that of a commercial vaccine as a positive control from National Veterinary Joint Stock company NAVETCO, Vietnam with the chicken protective rate of 90%. Whereas the chicken protection rate against A/H5N1 clade 1.1 virus of the H5TG trimer antigen was 50%. These results suggest that the IgMFc motif plays an important role in the forming of oligomeric proteins which had been proved for enhancing immunogenicity and protection ability in this study. Therefore, the plant-based oligomerized recombinant H5TG antigen is a potential vaccine candidate against A/H5N1 influenza virus in the future.